THE INFLUENCE OF CAPITAL BUDGETING METHODS ON THE FEASIBILITY OF COMPANY INVESTMENT: A LITERATURE REVIEW STUDY - Failasufa, Mila; Mukhtaruddin, Mukhtaruddin (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
The purpose of this study is to systematically analyze previous research on the application of capital budgeting methods and their impact on the feasibility of corporate investment. Using the Systematic Literature Review (SLR) approach, this study identifies, evaluates, and synthesizes findings from 24 scientific journals indexed by Scopus, Q1, Q4 and Sinta 4 and 5 for 11 years, from 2014 to 2025. The results of the study show that methods such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI) have a significant influence in increasing investment efficiency, risk management, and achieving feasibility in investment. This study contributes to enriching academic understanding and providing practical implications for corporate decision makers in optimizing investment strategies based on capital budgeting methods to increase competitiveness and financial growth.